PENGARUH PEMANFAATAN BONGGOL PISANG SEPATU (Musa paradisiaca L) DALAM RANSUM TERHADAP PERSENTASE KARKAS DAN LEMAK ABDOMINAL AYAM BROILER - Pontoh, Sulastri G.; Mandey, J.; Wolayan, F.R.; Kowel, Y. (ZOOTEC, 2019)
THE INFLUENCE OF THE USE OF BANANA HUMP SHOES (Musa paradisiaca L) IN RATION ON THE PERCENTAGE OF CARCASS AND ABDOMINAL FAT IN BROILER CHICKEN. This study aims to determine the extent of the effect of using banana hump shoes (Musa Paradisiaca) in rations on carcass and abdominal fat in broiler chickens. This study was conducted using 100 unsexed Cobb broiler chickens (PT. Charoen Pokhpand), with an average body weight of 837 grams. The design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. Arrangement of the experimental treatment as follows: Râ‚€= 55% corn + 0% banana hump shoes, Râ‚= 50% corn + 5% banana hump shoes, Râ‚‚= 45% corn + 10% banana hump shoes, Râ‚ƒ= 40% corn + 15% banana hump shoes. The results showed that there was no significant difference (P>0,05) on the percentage of carcass and abdominal fat in broiler chickens. Based on the results of this study it can be concluded that the use of banana shoe hump in rations up to 15% produces a good percentage of carcass and abdominal fat.Â Keywords: broiler chicken, banana hump shoes, percentage of carcass and abdominal fat.Â